Impact of unilateral spatial neglect on chronic patient's post-stroke quality of life - Ferreira Sobrinho, Keller Ricardo; Monteiro Santini, Ana Carolina; Sacomani Marques, Carlos Leonardo [UNESP]; Gabriel, Maicon Goncalves [UNESP]; Neto, Eduardo de Moura; Pascucci Sande de Souza, Luciane Aparecida; Bazan, Rodrigo [UNESP]; Luvizutto, Gustavo Jose (Taylor & Francis Ltd, 2018)
Background: Unilateral spatial neglect (USN) is the prevalent feature in patients with right-sided stroke. It is diagnosed through the behavior inattention test (BIT) and has a negative impact on patients affecting both their functional capacity and quality of life. Objective: Here, we aimed to evaluate the impact of USN on the quality of life of patients in the chronic phase of stroke. Methods: This is a cross-sectional study with stroke patients with USN. After confirming the presence of stroke through neuroimaging examinations and of USN through the BIT, patients' quality of life was evaluated by using the EUROQOL scale. Spearman's correlation was used to validate the correlation between patients' USN and quality of life, with a p<.05 representing significant results. Results: Eighteen individuals were included. When correlating the value of each domain of the EUROQOL scale with the results of the BIT, we observed a negative correlation between mobility (r = -0.97; p = .000), self-care (r = -0.82; p = .013), usual activities (r = -0.87; p = .005); pain or discomfort (r = -0.88; p = .004), anxiety or depression (r = -0.97; p = .000), and EUROQOL total score (r = -0.97, p = .000). Conclusion: After a correlation between the overall EUROQOL and BIT scores, we suggest that the higher the USN degree is in stroke patients, the worse their perceived quality of life tends to be.
Keywords: Stroke; chronic stroke; unilateral spatial neglect; quality of life